Fine structure of diffused pseudobranchial neurosecretory cells associated with carotid labyrinth in an air‐breathing catfish Clarias batrachus. (4th October 2014) - Sengar, Manvendra; Yadav, Laxmi; Gopesh, Anita; Zaccone, Daniele; Lauriano, Eugenia Rita; Capillo, Gioiele
Abstract: Fish are known to have branchial chemoreceptors and even extrabranchial chemoreceptors to meet the challenges of aquatic environment. The pseudobranchial neurosecretory system associated with carotid labyrinth (CL) is one such example. CL – a chemosensory organ is well known in amphibians. The homologous structure also exists in fish. Clusters of neurosecretory cells, close to the CL and the first two efferent branchial arteries occur in catfish and a few other groups of teleosts. These cells belong to the pseudobranchial neurosecretory system (PNS). To reveal the ultrastructure of CL and the pseudobranchial neurosecretory cells (PNSCs), environmental scanning electron microscope (ESEM) and transmission electron microscope (TEM) investigations were made in an Asian air‐breathing catfish Clarias batrachus . Under ESEM, the PNS appeared as a mass of cells innervated by nerves and supplied by blood capillaries. The CL appeared to have a network of blood capillaries. The transmission electron microscopic investigations showed pear shaped PNSCs having different sizes of dense cored vesicles (DCVs), numerous mitochondria, nerve varicosities, indicating a secretory function of the cells. The CL shows a close association with PNSCs and smooth muscles. Although the exact function of the CL and associated PNSCs in the biology of fish is far from clear, their morphology suggests they are involved in a stress response such as to hypoxia.